2020
DOI: 10.1111/jog.14535
|View full text |Cite
|
Sign up to set email alerts
|

Successful detection of rectal injury during laparoscopic surgery using a rectal probe in a patient with deep endometriosis

Abstract: Laparoscopic surgery has become the gold standard treatment for endometriosis. Surgical treatment of deep endometriosis with colorectal involvement is challenging. It requires complete surgical excision of lesions despite a high risk of complications that include rectal injury, rectovaginal fistula and pelvic abscess. An intraoperative air leak test allows detection of rectal injury and reduces postoperative complications. We report a case of successful management of rectal injury during laparoscopic surgery u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Among these injuries, the small intestine is the most commonly affected site (55.8%), followed by the large intestine (38.6%) and the stomach (3.9%) [20]. A study involving 12,354 patients undergoing laparoscopic surgery reported 15 cases of rectal injury [21]. In our study, one patient who had undergone two previous surgeries required transvaginal repair of a rectovaginal fistula, resulting in a yellow-green vaginal discharge.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 63%
“…Among these injuries, the small intestine is the most commonly affected site (55.8%), followed by the large intestine (38.6%) and the stomach (3.9%) [20]. A study involving 12,354 patients undergoing laparoscopic surgery reported 15 cases of rectal injury [21]. In our study, one patient who had undergone two previous surgeries required transvaginal repair of a rectovaginal fistula, resulting in a yellow-green vaginal discharge.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 63%
“…Surgical treatment of gynecological disease with colorectal involvement is a challenge which requires complete surgical excision of lesions. 1 Blind blunt dissection of the Douglas pouch might cause massive and rectal tissue damage. 2 3 Traditional hysterectomy may cause rectal injury for those cases with severe adhesion in the Douglas pouch.…”
mentioning
confidence: 99%